Endocytosis and Sphingolipid Scavenging in Leishmania mexicana Amastigotes - Hayder Z. Ali; Clare R. Harding; Paul W. Denny (Biochemistry Research International)
Leishmania species are the causative agents of the leishmaniases, a spectrum of neglected tropical diseases. Amastigote stage parasites exist within macrophages and scavenge host factors for survival, for example, Leishmania species utilise host sphingolipid for synthesis of complex sphingolipid. In this study L. mexicana endocytosis was shown to be significantly upregulated in amastigotes, indicating that sphingolipid scavenging may be enhanced. However, inhibition of host sphingolipid biosynthesis had no significant effect on amastigote proliferation within a macrophage cell line. In addition, infection itself did not directly influence host biosynthesis. Notably, in contrast to L. major, L. mexicana amastigotes are indicated to possess a complete biosynthetic pathway suggesting that scavenged sphingolipids may be nonessential for proliferation. This suggested that Old and New World species differ in their interactions with the macrophage host. This will need to be considered when targeting the Leishmania sphingolipid biosynthetic pathway with novel therapeutics.